Mengembangkan Media Pembelajaran Big Book untuk Meningkatkan Toleransi pada Siswa Sekolah Dasar - Nofry Vincensius Wongkar; Susan Noviaty Herienth Jacobus (Journal on Education, 2024)
Tolerance is a very important thing in life and in appreciating the differences that exist, tolerance must basically be instilled from school age how a child processes to know the differences that exist in their environment. The use of Big Book media is a special alternative as a media to introduce the diversity around so that students can understand what is meant by tolerance so that knowledge of tolerance can grow well by using Big Book media as a media to introduce tolerance. In this study used media R & D using a model developed by Brog and Gall, so that the discovery of the results of 96.5% of students better understand the material taught is about increasing tolerance among others so that it can be concluded that the use of Big Book media is very effective in introducing the material to be taught so that students can better understand and motivation to learn better.